IMPACT OF TEACHERS’ SOCIO-ECONOMIC STATUS ON THEIR STUDENTS’ ACADEMIC PERFORMANCE - Bhatti, Eiman; Qurat-ul-ain,; Tahira, Dr. Rifat (The journal of contemporary issues in business and government, 2021)
The study was conducted to see the impact of teachers’ socio-economic status on their students’ academic performance. The Study was descriptive in nature and survey method was employed to gather the desired data to fulfill the objectives of the study. Elementary school level teachers were the population of the study. After reviewing the literature, questionnaire for teachers’ was designed. Six hundred and 28 teachers fromelementaryschool levelwere selected randomly. Gathered data were systematically arranged, and coded for the purpose of analysis. Arranged data was analyzed by applying the descriptive and inferential statistics. Frequencies and percentage was extracted for descriptive statistics and one way ANOVA was employed to find the impact of teachers’ SES on their students’ academic performance. Major findings of the study revealed that their teachers’ qualification, monthly family income and level of institution also influenced on the performance of their students. On the basis of findings it was suggested that educational institutes should arrange the behavior modification trainings for teachers and take the responsibility to improve teachers socio-economic status.